Modeling the associations between L2 teacher support and EFL learners’ reading motivation: The mediating impact of reading enjoyment, anxiety, and boredom - Derakhshan, Ali; Solhi, Mehdi; Dewaele, Jean-Marc; Shakki, Farzaneh (Studies in Second Language Learning and Teaching, 2025)
The present study aimed to explore the association between 302 (93 males and 209 females) English as a foreign language (EFL) learners’ perceived teacher support (i.e., personal support and academic support) and their reading motivation. This inquiry also sought to assess the potential mediating influences of second or foreign language (L2) boredom, anxiety, and enjoyment on the interplay between the constructs under investigation. The results indicated a significantly strong and positive relationship between personal and academic teacher support and reading motivation. While L2 reading boredom and anxiety exhibited strong negative correlations with the two facets of teacher support, L2 enjoyment was positively correlated. Additionally, L2 reading enjoyment displayed a strong association with reading motivation. The results also revealed that over half of the variance in L2 reading motivation could be predicted by teacher support, along with the mediating influences of learner emotions. The findings are discussed in connection with educational theories, and implications are drawn for teaching.